Multi-objective geometry optimization of the Fish Bone Active Camber morphing airfoil. (April 2016) - Woods, Benjamin KS; Friswell, Michael I
This work presents the development of a design optimization code for the geometry of the Fish Bone Active Camber morphing airfoil concept, which has been under development at Swansea University. This concept employs a biologically inspired architecture to provide highly anisotropic structural compliance, which creates smooth and continuous camber changes of large magnitude. Previous work has shown that this concept is capable of large lift coefficient control authority and significant reductions in drag over traditional trailing edge flaps. Further development of the concept requires a more robust design methodology that allows for an automated and thorough search of the available design space in order to optimize the aero-structural and system-level performance of the concept. To this end, this research extends a previously developed fluid–structure interaction analysis into a useful design tool by embedding it within a multi-objective structural optimization routine based on a genetic algorithm. The three objective functions of aerodynamic drag, added mass, and actuation energy are minimized concurrently. Example results from a specific operating condition are shown. Examination of the Pareto frontiers and the objective values of the population at large give insight into the structural behavior of the morphing concept. The objectives of mass and energy are found to be strongly competing, but good compromise points exist. The drag objective is found to be less sensitive than the others, with low drag being achievable across a range of designs with both low mass and low energy requirements, although the Pareto frontiers formed are not as well populated with regard to drag.